Israel : Background Studies, Information Notes, and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This paper reviews economic developments in Israel during the 1990s. The paper analyzes tax revenue shortfalls in 1995-97. The factors that have contributed to overruns in the budget deficit relative to its targeted level are examined. The analysis indicates that the main difficulty has stemmed from the revenue side, and details the various areas where problems have occurred. The paper examines whether stable estimating equations for the major tax components can be established. The paper also examines volatility of interest rates in Israel.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet